2015
DOI: 10.1136/archdischild-2015-310148.48
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Adverse Drug Reaction Reports for Neonates and Infants in the Uk 2001–2010

Abstract: AimsThe UK Medicines and Healthcare products Regulatory Agency (MHRA) runs a national spontaneous reporting system (Yellow Card Scheme [YCS]) to collect ‘suspected' adverse drug reaction (ADR) data. We aim to describe the Yellow card reports received for patients aged ≤1 year for a 10 year period and assess their utility.MethodsData on all ADRs reported via the YCS in Infants aged ≤1 years from the years 2001–10 were supplied by the MHRA.ResultsIn total, 3217 suspected ADRs were reported to the YCS between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Comparable to previously reported retrospective studies, over 70% of patients in our study reported EVE-related AEs, which were more frequently reported (80%) among the adult cohort than among children and adolescents (59%) [18,57,81]. In addition to a potential increased willingness to report AEs among adult patients, the underestimation of AEs among children and adolescents due to by-proxy recording of AEs based on the responses of parents and guardians may be a factor in this difference, although this appears to be unlikely according to the literature [82,83]. In line with the most pivotal and post-marketing studies, frequently reported AEs included stomatitis, symptoms of immunosuppression, trivial infections and an acne-like rash [17,18,51].…”
Section: Discussionmentioning
confidence: 57%
“…Comparable to previously reported retrospective studies, over 70% of patients in our study reported EVE-related AEs, which were more frequently reported (80%) among the adult cohort than among children and adolescents (59%) [18,57,81]. In addition to a potential increased willingness to report AEs among adult patients, the underestimation of AEs among children and adolescents due to by-proxy recording of AEs based on the responses of parents and guardians may be a factor in this difference, although this appears to be unlikely according to the literature [82,83]. In line with the most pivotal and post-marketing studies, frequently reported AEs included stomatitis, symptoms of immunosuppression, trivial infections and an acne-like rash [17,18,51].…”
Section: Discussionmentioning
confidence: 57%